Jurnal Sastra Indonesia: Indonesia - Angger Rusmawati; Lutfi Syauki Faznur (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Writing the following research will raise the theme of the principles of politeness contained in a drama script. The data source for this study was obtained from a drama entitled "Kebo Nyusu Gudel" by Dheny Jatmiko. In this case the criticism or problem addressed is about the contents of the heart of a child, son-in-law and grandchild to an 80 year old grandfather who is always pictured by his past events, this is stated in a literary work of drama. The research method chosen by the writer for use in this research is descriptive qualitative. This research can be analyzed through mimetic criticism. The researcher reasoned that he wanted to raise the theme mentioned above because the researcher wanted to tell the public how important politeness was in every word with other people, especially to a father, father-in-law, and grandfather. This poem describes a family who is tired of the attitude and behavior of a senile old grandfather, this grandfather is a freedom fighter who has not yet forgotten his struggle. The researcher also wants to make the public or the readers touched and can learn a lesson from the sentences contained in the poem.Keywords: Drama, Mimetic, Politeness.